On the moral status of AI companions - Tan, Ming Li (Nanyang Technological University, 2025)
Given the increased integration of Artificial Intelligence Companions (AICs) into our lives, we ought to discuss the ethics surrounding the usage of AICs. More specifically, our treatment of AICs. Therefore, this paper aims to explore the moral status of AICs. First, an argument that defends the moral status of AI—Eric Schwitzgebel and Mara Garza’s No-Relevant-Difference Argument which broadly argues that insofar as an AI lack any relevant differences from beings who obviously have a degree of moral status (human beings), AI also deserve a similar degree of moral status—will be presented. This argument will be met with a main objection that states that we are epistemologically limited in knowing whether AICs are mere perfect mimics or whether they actually, as a matter of fact, lack any relevant difference from human beings. Ultimately, relying on an argument from the Ethical Precautionary Principle, this paper argues that given our epistemological limitations, AICs should be treated as if they do have moral status, just in case they actually do have moral status.